Penatalaksanaan Nyeri Persalinan dan Fasilitasi Penurunan Kepala Janin melalui Counterpressure dan Birthing Ball: Laporan Asuhan Kebidanan Persalinan Komprehensif pada Ny. S Umur 26 Tahun G2P1A0 di Klinik Tri Karya - Lisjarwati; Vistra Veftisia (Universitas Ngudi Waluyo, 2025)
Childbirth is a physiological process often accompanied by significant pain, which, if not properly managed, can increase maternal stress and the risk of medical interventions. Non-pharmacological techniques, such as counterpressure and the use of a birthing ball, are complementary interventions aimed at stimulating endorphin release and utilizing gravity to accelerate fetal head descent. This study aims to provide comprehensive midwifery care for Mrs. S, focusing on labor pain management and facilitating fetal head descent through counterpressure and birthing ball methods. The research instrument utilized a descriptive approach, documented in the SOAP (Subjective, Objective, Assessment, Planning) format. Data were collected through interviews, observations, physical examinations, diagnostic tests, documentation, and literature reviews. The study was conducted from June 2025 to October 2025. Results showed that during the active phase of the first stage of labor, Mrs. S reported significant lower back pain. Following the intervention of counterpressure during contractions and vertical pelvic movements using a birthing ball, the patient felt more relaxed and comfortable. The total duration of the first stage of labor from 3 cm dilation to complete dilation was 5 hours. The infant was delivered spontaneously and healthy, without perineal lacerations; the fetal position descended effectively into the pelvic area and stimulated productive contractions. Based on the comprehensive midwifery care report for Mrs. S, a 26-year-old (G2P1A0) at the Tri Karya Clinic, the researcher concluded that the combination of counterpressure and birthing ball techniques is effective in reducing labor pain intensity (back labor) and accelerating the duration of the first stage of labor by optimizing pelvic diameter and utilizing gravity. Midwives are expected to implement these methods as a standard of